DEVELOPMENT OF MATHEMATICS LEARNING MEDIA APPLICATION OF LOGARITHM BASED ON FRAMEWORK7 - Safiil Maarif; Firdha Rohmatul Auliyah (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
Learning carried out by a teacher can be facilitated by the existence of learning media. Learning media serves as a learning aid for students and can be used as a presentation of information on the subject matter, practice questions, or both. Current learning media can be in the form of applications that can be accessed via an Android smartphone. The purpose of this study was to develop logarithmic mathematics learning media using framework7. Framework7 is specifically intended for building hybrid-based mobile applications. The research method used in this research is research and development or Research and Development (R&D). The research design refers to Thiagarajan's research model which has 4 steps (4D), namely define, design, development, and dissemination. This study used data collection instruments in the form of validation sheets from media experts and material experts as well as a questionnaire regarding the logarithmic material learning media trials. According to the results of the development of learning media, it has five components, namely the home page, logarithmic menu list, logarithmic material interface, AP-LOG interface, quiz interface. There are three stages of learning media trials in this study, namely individual trials, small group trials, and large group trials. The results of the testings of instructional media for teachers and students get the results of 10 indicators. so that the learning media are classified under the criteria